Conservative surgery of breast cancer in women; psychological benefits - Răzvan V. Scăunașu; Traean Burcoș; Ștefan Voiculescu; Bogdan Popescu; Șerban V. Berteșteanu; Oana-Denisa Bălălău; Nicolae Bacalbașa; Cristian Bălălău (Journal of Mind and Medical Sciences)
Breast surgery was one of the most dynamic fields of medicine which benefited from significant progress during the last decades. The transition from aggressive and mutilating amputations to conservative, oncoplastic and reconstructive techniques has been constant, offering improved and rewarding results, viewed from both, oncological and aesthetical perspectives. Conservative techniques, especially those which preserve the nipple areola complex, are followed by improved patient’s perception of their body image, confidence and sexuality, with the only drawback of increased anxiety linked to recurrence risk.